Effects of Frame Rate on Two‐Dimensional Speckle Tracking–Derived Measurements of Myocardial Deformation in Premature Infants. Issue 5 (11th August 2014) - Sanchez, Aura A.; Levy, Philip T.; Sekarski, Timothy J.; Hamvas, Aaron; Holland, Mark R.; Singh, Gautam K.
Abstract : Background: Frame rate (FR) of image acquisition is an important determinant of the reliability of 2‐dimensional speckle tracking echocardiography (2DSTE)‐derived myocardial strain. Premature infants have relatively high heart rates (HR). The aim was to analyze the effects of varying FR on the reproducibility of 2DSTE‐derived right ventricle (RV) and left ventricle (LV) longitudinal strain (LS) and strain rate (LSR) in premature infants. Methods: RV and LV LS and LSR were measured by 2DSTE in the apical four‐chamber view in 20 premature infants (26 ± 1 weeks) with HR 163 ± 13 bpm. For each subject, 4 sets of cine loops were acquired at FR of <90, 90–110, 110–130, and >130 frames/sec. Two observers measured LS and LSR. Inter‐ and intra‐observer reproducibility was assessed using Bland–Altman analysis, coefficient of variation, and linear regression. Results: Intra‐observer reproducibility for RV and LV LS was higher at FR >110 frames/sec, and optimum at FR >130 frames/sec. The highest inter‐observer reproducibility for RV and LV LS were at FR >130 and >110 frames/s, respectively. The highest reproducibility for RV and LV systolic and early diastolic LSR was at FR >110 frames/sec. FR/HR ratio >0.7 frames/sec per bpm yielded optimum reproducibility for RV and LV deformation imaging. Conclusions: The reliability of 2DSTE‐derived RV and LV deformation imaging in premature infants is affected by the FR of image acquisition. Reproducibility is most robust when cine loops are obtained with FR/HR ratio between 0.7 and 0.9 frames/sec per bpm, which likely results from optimal myocardial speckle tracking and mechanical event timing.